Automatic Calibration of Robotic Manipulator - Yuan, Qilong (2016)
Robot calibration is an efficient way to improve the accuracy of robots. In earlier robot calibration which depends on dozen of manual measurements of the robot poses, the calibration procedure is less efficient. With the new measurement technologies like optical capture system, the laser tracker etc., the measurements of the robot poses can be conducted automatically. This paper introduced a fully automatic calibration process using the optical capture system as an example. To demonstrate the automatic calibration, the calibration process of a six-DOF modular robot using optical capture systems with eight cameras is conducted. A robot calibration method with minimal calibration parameters is applied for the calibration. Using the optical capture system with a position accuracy of about 1mm, the manipulating accuracy of the robot is increased from centimeter level to 3 mm after the calibration. With the advanced tracking technologies, such automatic calibration is nowadays very useful in avoiding the measurement errors from human and speeding up the manipulation process.